Porous Carbon Fibers Containing Pores with Sizes Controlled at the Ångstrom Level by the Cavity Size of Pillar[6]arene. Issue 22 (23rd April 2015) - Ogoshi, Tomoki; Yoshikoshi, Kumiko; Sueto, Ryuta; Nishihara, Hirotomo; Yamagishi, Tada‐aki
Abstract We report a new synthesis method of fibrous carbon material with pores sizes that are precisely controlled at the Ångstrom level, by carbonization of two dimensional (2D) porous sheets of pillar[6]arenes. The 2D porous sheets were prepared by 2D supramolecular polymerization induced by oxidation of hydroquinone units of pillar[6]arenes. Owing to the hexagonal structure of pillar[6]arene, the assembly induced by 2D supramolecular polymerization gave hexagonal 2D porous sheets, and the highly ordered structure of the 2D porous sheets formed regular fibrous structures. Then, carbonization of the 2D porous sheets afforded fibrous carbon materials with micropores. The micropore size of the fibrous porous carbon prepared from pillar[6]arene was the same size as that of the starting material pillar[6]arene assembly.